Silver bullet or not? The impact of agricultural biotechnology on the right to food in Africa - Eshete, Mandefro (University of Pretoria, 2006)
Prepared under the supervision of Dr. Mandefro Eshete at the Faculty of Law, Addis Ababa University, Ethiopia